Evolution of plumes from a composite plate–cylinder heat source under buoyancy–shear driven conditions - Ningbin Zhu; Yang Yang; Mengdan Qiao; Yi Wang; Qingfeng Cao; Yong Cui; Yuming Zhang; Sikang Li (Building and Environment, 2026)

Resistance characteristics of irregular exhaust hoods and inverse design based on airflow distribution in rolling mills - Qingfeng Cao; Yang Yang; Zhaolan Zhang; Yi Wang; Kangning Xiong; Yong Cui; Yuming Zhang; Sikang Li; Ning Lei (Journal of Cleaner Production, 2026)

Synergistic optimization of filter bag arrangement and shape for vortex suppression flow equalization and resistance reduction in a straight-through baghouse dust collector - Qingfeng Cao; Yang Yang; Yi Wang; Kangning Xiong; Ningbin Zhu; Yong Cui; Yuming Zhang; Sikang Li (Journal of Cleaner Production, 2026)

Early Holocene monsoon abrupt changes and hydrological response as recorded by a multi-proxy stalagmite from Yuquan Cave, Central China - Xiaomeng Cui; Junji Zhu; Kan Zhao; Jiangying Wu; Yijia Liang; Liang Ning; Qingfeng Shao; Yongjin Wang (Science China Earth Sciences, 2026)

Pressure drop reduction of filter media for oily aerosol: progress and prospects - Yong Cui; Yang Yang; Kangning Xiong; Yi Wang; Qingfeng Cao; Sikang Li; Yuming Zhang (Energy and Buildings, 2026)

Diffusion of micron-sized oil droplets accompanying short-term thermal airflow with weak buoyancy in machining intervals - Yuming Zhang; Yang Yang; Yi Wang; Jia-ning Fan; Tongtong Zhao; Jun Gao; Qingfeng Cao; Ningbin Zhu; Yong Cui (Building and Environment, 2026)

Double-plunging structure of the Bond 4 event evidenced in new mid-Holocene stalagmite records from northern China - Quan Wang; Yingfang Cui; Kan Zhao; Jianshun Chen; Qingfeng Shao; Jianghu Lan; Liangcheng Tan; Lei Ding; Hongan Dong; Lili Dai; Yongjin Wang (Global and Planetary Change, 2025)

Integrated Analysis of Phenotypic and Hepatic Transcriptomic Profiles Reveals Enhanced Cold Tolerance in Triploid Crucian Carp - Suifei Tao; Zexun Zhou; Shandong Chen; Jialin Cui; Yude Wang; Kaikun Luo; Wei Liu; Qingfeng Liu; Wuhui Li; Shaojun Liu (Fishes, 2025)
Cold stress poses a critical threat to fish survival by triggering metabolic dysfunction, oxidative damage, immune suppression, and apoptosis. However, hybrid polyploid fish triploid crucian carp (3nRCR, 3n = 150) demonstrate superior stress tolerance. In this study, we investigated the cold adaptation mechanisms in different ploidy cyprinid fishes: triploid crucian carp compared to its diploid improved red crucian carp (Carassius auratus red var., RCC, 2n = 100, ♀) and improved allotetraploid (4nAT, 4n = 200, ♂) progenitors. Under controlled cooling, 3nRCR lost equilibrium at a significantly lower temperature (3.2 °C) than RCC (4.0 °C) and 4nAT (4.5 °C), confirming its superior enhanced cold resistance. Histological examination revealed minimal tissue damage in 3nRCR, characterized by reduced gill inflammation and cellular apoptosis. Transcriptomics revealed triploid-specific molecular strategies: 3nRCR uniquely activated retinol metabolism and metabolic rewiring (arginine/proline metabolism, oxidative phosphorylation). Notably, in the immune-related NLR signaling pathway, both nlrp1 and nlrp3 (key inflammasome components) were significantly downregulated in 3nRCR (p

Ultrasound triggered spatial-temporal NO gas release to enhance sonodynamic therapy and immune checkpoint blockade therapy against pancreatic cancer - Wanrui Shi; Jianfeng Zhang; Ruiqi Wu; Shiti Shama; Shi Tan; Heng Xue; Yan Sun; Qingshuang Tang; Suhui Sun; Rui Tang; Guotao Feng; Xiaoda Li; et al. (Chemical Engineering Journal, 2025)

Decrypting gene-spliced like and fast kinetic energy storage modes of Na/Mg dual doped manganese oxides cathode for high-performance aqueous zinc-ion batteries - Xiaosha Cui; Yaxiong Zhang; Qingfeng Wu; Sida Deng; Shengyuan Wang; Jiuzhou Wang; Yupeng Liu; Junli Zhang; Erqing Xie; Jiecai Fu (Chemical Engineering Journal, 2025)

Evaporation and settling of semi-synthetic metalworking fluid droplets in industrial buildings - Yuming Zhang; Yang Yang; Qingfeng Cao; Ningbin Zhu; Yong Cui; Yi Wang; Chaojie Wang (Building and Environment, 2025)

Alterations in microbial community structures and metabolic function in soil treated with biological and chemical insecticides - Renwen Zheng; Jun Peng; Qianqian Li; Yue Liu; Dongyan Huang; Yangjunlu Sheng; Cui Liu; Lei Qi; Nemat O. Keyhani; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2025)

Biosurfactants are green and versatile enhancers for sustainable treatment of oily sludge: A review - Feng Zhao; Qingfeng Cui; Han Su; Chunyan Li; Mei Dong (Journal of Environmental Chemical Engineering, 2025)

Stomatin-like protein 2 promotes cell proliferation and survival under 5-Fluorouracil stress in hepatocellular carcinoma - Xiaoqi Li; Yahui Zheng; Kangkang Yu; Sen Hou; Huxiao Cui; Ruiqi Yin; Yu Zhou; Qingfeng Sun; Jubo Zhang; Chong Huang (Molecular Biology Reports, 2024)

Orbital- and millennial-scale hydroclimate changes in central China during the last glacial period - Quan Wang; Kan Zhao; Yongjin Wang; Jianshun Chen; Yijia Liang; Yingfang Cui; Qingfeng Shao; Xiumin Zhai; Zhenqiu Zhang; Xinggong Kong; Hai Cheng; R. Lawrence Edwards; et al. (Quaternary Science Reviews, 2024)

Fabrication of Supramolecular System Derived from Poly β-cyclodextrin Coupling Quinoline Dderivative and Its Fluorescence Sensing of Zinc Ion in Pure Water Environment - Wenping Zhu; Yinlong Chen; Zengchen Liu; Weijie Yang; Yanxia Li; Yahong Chen; Qingfeng Li; Yali Cui; Baodui Wang (Journal of Fluorescence, 2023)

Methamphetamine induces cardiomyopathy through GATA4/NF-κB/SASP axis-mediated cellular senescence - Xu Zhao; Jiancong Lu; Cui Zhang; Chuanxiang Chen; Manting Zhang; Jingyi Zhang; Qingfeng Du; Huijun Wang (Toxicology and Applied Pharmacology, 2023)

Comparison of a fuzzy control and the data-driven model for flood forecasting - Yixiang Sun; Deshan Tang; Yifei Sun; Qingfeng Cui (Natural Hazards, 2016)

Spectroscopic, Viscositic and Molecular Modeling Studies on the Interaction of 3′-Azido-Daunorubicin Thiosemicarbazone with DNA - Fengling Cui; Qingfeng Liu; Hongxia Luo; Guisheng Zhang (Journal of Fluorescence, 2014)

The benefits of recent warming for maize production in high latitude China - Qingfeng Meng; Peng Hou; David B. Lobell; Hongfei Wang; Zhenling Cui; Fusuo Zhang; Xinping Chen (Climatic Change, 2014)

Closing the yield gap could reduce projected greenhouse gas emissions: a case study of maize production in C hina - Zhenling Cui; Shanchao Yue; Guiliang Wang; Qingfeng Meng; Liang Wu; Zhiping Yang; Qiang Zhang; Shiqing Li; Fusuo Zhang; Xinping Chen (Global Change Biology, 2013)
Although the goal of doubling food demand while simultaneously reducing agricultural environmental damage has become widely accepted, the dominant agricultural paradigm still considers high yields and reduced greenhouse gas ( GHG ) intensity to be in conflict with one another. Here, we achieved an increase in maize yield of 70% in on‐farm experiments by closing the yield gap and evaluated the trade‐off between grain yield, nitrogen (N) fertilizer use, and GHG emissions. Based on two groups of N application experiments in six locations for 16 on‐farm site‐years, an integrated soil‐crop system ( HY ) approach achieved 93% of the yield potential and averaged 14.8 Mg ha −1 maize grain yield at 15.5% moisture. This is 70% higher than current crop ( CC ) management. More importantly, the optimal N rate for the HY system was 250 kg N ha −1 , which is only 38% more N fertilizer input than that applied in the CC system. Both the N 2 O emission intensity and GHG intensity increased exponentially as the N application rate increased, and the response curve for the CC system was always higher than that for the HY system. Although the N application rate increased by 38%, N 2 O emission intensity and the GHG intensity of the HY system were reduced by 12% and 19%, respectively. These on‐farm observations indicate that closing the yield gap alongside efficient N management should therefore be prominent among a portfolio of strategies to meet food demand while reducing GHG intensity at the same time.

Spectroscopic and Molecular Modeling Studies of the Interaction Between 4′-O-(α-L-Oleandrosyl)daunorubicin and Human Serum Albumin and Its Analytical Application - Ruina Huo; Cui Li; Fengling Cui; Guisheng Zhang; Qingfeng Liu; Xiaojun Yao (Journal of Fluorescence, 2012)